Chlamydia-like organisms in ctenidia and mantle cells of the Japanese oyster Crassostrea gigas from the French Atlantic coast - Renault, Tristan; Cochennec, Nathalie (Diseases of Aquatic Organisms, 1995)
Grossly visible lesions of the ctenidia and occasional mortalities in Japanese oyster Crassostrea gigas from the Atlantic French coast were reported in 1992-1993. From August 1992 to March 1993, 235 living oysters were collected to determine the cause of tissue lesions and mortalities. Microscopical examination of fixed, stained sections revealed that 53.2% of these oysters had ctenidia and mantle lesions associated with irregular basophilic and Feulgen positive cytoplasmic inclusion bodies. Ultrastructurally, the infectious agent was a chlamydia-like organism. Indirect fluorescent and peroxidase conjugated antibody tests suggested that this agent might share common antigens with the procaryotic agent Chlamydia psittaci, strain ovis.